The Effect of Discussion Methods and Differentiation Strategies on Students' Speaking Ability in Learning Indonesian Languageat Sendawar State Senior High School - Imas Komala; Ayu Khairiyah; Ventje Jany Kalukar; Susilo (Arbain Publishing, 2025)
This aiming For know influence method discussion and differentiated strategies to ability speak student in Indonesian language learning at Sendawar State High School. Background study This leave from low participation active and ability speak student in activity learning, which is suspected influenced by the approach lack of learning varied and not consider difference characteristics students. The method used in study This is quantitative with approach experiment quasi -experimental design, involving two classes as group experiments and controls . Instruments study in the form of test ability talk and sheet observation activity students. Research results show that implementation method combined discussion with a differentiated strategy give influence positive and significant to improvement ability speak students. Findings This show that approach adaptive and participatory learning capable increase skills communication oral student in a way effective in context Indonesian language learning.